A new inhibitor of human peptide deformylase suppresses cell proliferation and induces cell apoptosis and autophagy in cancers. Issue 4 (18th April 2023) - Guo, Yanzhi; Han, Yuqiao; Li, Ziyan; Ji, Jiali; Zhu, Tong; Du, Yijie; Dong, Suzhen
Abstract : Human peptide deformylase (hsPDF) has been found overexpressed in many cancer cells and its inhibitors exhibit antitumor activity. Studies were performed to validate that hsPDF is a good antitumor target. The inhibitory effect of PDF64 on hsPDF enzymatic activity was measured and confirmed by computation analysis. Antiproliferation activity was determined and in-vivo antitumor activity were analyzed in HCT116 and HL60 nude mice xenografts. Mitochondrial membrane potential (MMP), cell apoptosis, and autophagic cell death were analyzed by flow cytometry. ATP level was quantified using an ATP assay kit. Protein expression and kinase phosphorylation were determined by western blotting. A new hsPDF inhibitor PDF64 was identified. It showed evident antiproliferation activity in 10 cancer cells and significantly suppressed tumor growth in HCT116 and HL60 xenografts. It induced an obvious decrease in MMP and caused apparent cell apoptosis and autophagy in HCT116 and Jurkat cells. PDF64 treatment also led to an evident decrease in cellular ATP levels in these cells. Moreover, PDF64 downregulated c-Myc expression and had some effects on extracellular regulated protein kinases (ERK) and protein kinase B (Akt)/ mammalian target of rapamycin (mTOR) pathways. PDF64 exhibited good antitumor effects both in vivo and in vitro . It caused cell apoptosis and autophagic death in HCT116 and Jurkat cells. The effects may be mediated by inhibiting c-Myc expression and ERK or PI3K-Akt-mTOR pathway. Therefore, PDF64 may be a promising reagent for antitumor drug development, which further supports that hsPDF is a good antitumor drug target.